Preservation as a Service for Trust (PaaST) dalam Penjagaan Keaslian dan Keamanan Arsip Digital - Nurul Habib Romadhan; Tamara Adriani Salim (Yayasan Literasi Sains Indonesia, 2026)
Preservation as a Service for Trust (PaaST) is an innovative approach to digital archive preservation that integrates technical, policy, and audit functions into a trust-based managed service model. Given the increasing volume of digital data and the risks of format degradation and cybersecurity, PaaST exists to ensure the authenticity, integrity, and trustworthiness of long-term archives. This study uses a Systematic Literature Review (SLR) approach to identify trends, practices, and challenges in PaaST implementation from 2019 to 2025. The literature search process was conducted on various academic databases and institutional documents related to digital preservation standards such as OAIS (ISO 14721), ISO 16363 trusted repository certification, and the application of cryptography and blockchain technology for authenticating archives. The review results indicate that the managed digital preservation service model is increasingly being adopted by large archives and libraries because it is considered efficient, secure, and sustainability-oriented. The use of fixity check mechanisms, digital signatures, and timestamping (both blockchain-based and non-blockchain-based) has been proven to improve data integrity and the evidentiary value of archives. However, key challenges remain: financial sustainability, compliance with standards, and limited technical resources in small institutions. This article emphasizes the importance of synergy between technology, institutional policies, and long-term governance in PaaST implementation.